Pharmacological utilization of bergamottin, derived from grapefruits, in cancer prevention and therapy - Ko, J.; Arfuso, Frank; Sethi, G.; Ahn, K. (MDPI AG, 2018)
In spite of significant advances in treatment options and the advent of novel targeted therapies, there still remains an unmet need for the identification of novel pharmacological agents for cancer therapy. This has led to several studies evaluating the possible application of natural agents found in vegetables, fruits, or plant-derived products that may be useful for cancer treatment. Bergamottin is a furanocoumarin derived from grapefruits and is also a well-known cytochrome P450 inhibitor. Recent studies have demonstrated potent anti-oxidative, anti-inflammatory, and anti-cancer properties of grapefruit furanocoumarin both in vitro and in vivo. The present review focuses on the potential anti-neoplastic effects of bergamottin in different tumor models and briefly describes the molecular targets affected by this agent.